(untitled) (Research, Society and Development, 2025)
The definition of physical activity is understood as any voluntary body movement produced by the skeletal muscles, resulting in energy expenditure that is above resting levels. Therefore, physical exercises are understood as a subset of planned, structured and repetitive physical activity that aims to improve and maintain physical conditioning or improve health. Objective: to understand the practice of regular physical activity and the impacts on the individual’s preventive health. Methodology: Integrative review of qualitative and quantitative nature. Results: a synthesis of the distributions of scientific productions on the practice of regular physical activity was made. Thus, 20 authors were identified (16 journals and 4 books on Scientific Methodology). Final considerations: The impact on preventive health, regular physical activity is recommended to keep the individual active. Therefore, several benefits are proven for health prevention. Thus, the regular practice of physical activity is a determinant for health promotion and reduction of the risk of diseases in different age groups.